DIGITAL MARKETING MENTORING, BRAND POSITIONING, AND PACKAGING DEVELOPMENT STRATEGY FOR MSME “BAPAKE STIK KENTANG JOGJA” - lulu fatin athifah athifah; Yesika Serlanova; Andang Panji Nugroho; Agus Dwi Cahya; Fitriya Fauzi (EMPOWERING HUMANITY, 2026)
The rapid advancement of digital technology compels MSMEs to adapt by leveraging social media as an effective marketing tool. Bapake Stik Kentanga culinary micro-enterprise located at Jl. Prof. DR. Soepomo SH No. 72A, Warungboto, Umbulharjo, Yogyakarta possesses strong market potential but has yet to optimize digital marketing or establish a clear brand positioning to differentiate itself from competitors. This study aims to analyze strategies for using TikTok as a promotional medium to boost brand awareness while strengthening the brand's identity as a crispy, savory, and youth-oriented local snack. A qualitative approach utilizing Participatory Action Research (PAR) was employed, involving observation, interviews, mentoring, and content performance evaluation. The results indicate that creating content such as product reviews, storytelling, behind-the-scenes production footage, and local culinary recommendations can significantly expand audience reach and enhance user engagement. Uploaded content garnered over 8,000 views in the first week, accompanied by an increase in new followers. These findings confirm that a TikTok-based digital marketing strategy, when combined with strong brand positioning, is highly effective in increasing MSME visibility at a low cost.